2022
DOI: 10.1002/ange.202113653
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Highly Efficient Photothermal Conversion with Stable Open‐Shell Aromatic Nitric Acid Radicals

Abstract: It is very challenging to prepare stable radicals as they are usually thermodynamically or kinetically unstable in air. Herein, a series of star-shaped aromatic nitric acid radicals were prepared via facile demethylation and consequent oxidation. As phenol radicals without steric hindrance group protection, they exhibit high electrochemical and thermal stability due to their rich resonance structures including closed-shell nitro-like and open-shell nitroxide structure with unpaired electrons delocalized in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…The proposed 2D spin modules are designed based on AIARs through manipulating the electronic spin states of radicals on the benzene ring, thiophene, and other aromatic rings. The ANARs have been prepared in our group and confirmed to have application potential in the fields of photothermal and energy storage [8][9][10][11][12] .…”
Section: Background and Originality Contentmentioning
confidence: 93%
See 2 more Smart Citations
“…The proposed 2D spin modules are designed based on AIARs through manipulating the electronic spin states of radicals on the benzene ring, thiophene, and other aromatic rings. The ANARs have been prepared in our group and confirmed to have application potential in the fields of photothermal and energy storage [8][9][10][11][12] .…”
Section: Background and Originality Contentmentioning
confidence: 93%
“…A large number of narrow bandgap D-A type organic semiconductors, such as aromatic inorganic acid radicals (AIARs), have been prepared and demonstrated that the radical signal originates from the intrinsic open-shell quinone radical electronic ground state 5 . Although the AIARs share diradical characteristics with previously reported diradicaloids such as diindeno[b ,i ] anthracene and zethrene (restore aromaticity) [6][7] , the resonance mechanism of AIARs is transformed from aromatic type to quinone type (destroy aromaticity) 5,[8][9][10] , which may endow them with different physical characteristics.…”
Section: Background and Originality Contentmentioning
confidence: 97%
See 1 more Smart Citation
“…When oxygencontaining functional groups are introduced, non-radiative recombination of light-irradiated electrons is induced, which can promote fluorescence quenching and heat release. 102 For carbonaceous materials and some conjugated polymers (e.g., polypyrrole and polydopamine), although the transition from σ to σ* is impossible under solar light due to the large energy gaps, the loosely bonded electrons in the π orbital can be easily excited to the π* orbital with a smaller energy input, especially when the π bonds are conjugated, which induces the red-shift of the absorption spectrum and further narrows the energy gap between the ground state (highest occupied molecular orbital, HOMO) and the excited state (lowest unoccupied molecular orbital, LUMO). The excited electrons are relaxed by electron-phonon coupling, thereby generating lattice vibration, which facilitates the photothermal conversion (Fig.…”
Section: Thermal Vibration Of Moleculesmentioning
confidence: 99%
“…1) and benzodithiophene had a higher V OC of 0.86 V and improved power conversion efficiency (PCE) up to 5.06% in PSCs [41]. Our group has a long-standing interest in the design and synthesis of semiconducting polymers based on HH-linked dialkoxybithiophenes [42][43][44]. We recently functionalized the HH-linked dialkoxybithiophene (BT HH , Fig.…”
Section: Introductionmentioning
confidence: 99%